Řešení proudění v lidském oku - Pavlů, Karel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
The vitreous cavity, the largest chamber of the eye, is delimited anteriorly by the lens and posteriorly by the retina and is filled by the vitreous humour. Under normal conditions the vitreous humour has the consistency of a gel, however, typically, with advancing age a disintegration of the gel structure occurs, leading to a vitreous liquefaction. Moreover, after a surgical procedure called vitrectomy the vitreous body may be completely removed and replaced by tamponade fluids. Besides allowing the establishment of an unhindered path of light from the lens to the retina, the vitreous also has important mechanical functions. In particular, it has the role of supporting the retina in contact to the outer layers of the eye, and of acting as a diffusion barrier for molecule transport between the anterior and the posterior segments of the eye. Studying the dynamics of the vitreous induced by eye rotations (saccadic movements) is important in connection of both the above aspects. On the one hand indications exist that the shear stress exerted by the vitreous on the retina may be connected with the occurrence of retinal detachment. On the other hand, if the vitreous motion is intense enough (a situation occurring either when the vitreous is liqueed or when it has been replaced with a uid after vitrectomy), advective transport may be by far more important than diffusion and may have complex characteristics. Advection has indeed been shown to play an important role in the transport phenomena within the vitreous cavity, but, so far, only advection due to the slow overall fluid ux from the anterior to the posterior segments of the eye has been accounted for, while fluid motion due to eye rotations, even if it is generally believed to play an important role, has been invariably disregarded. Some recent contributions have pointed out the importance of accounting for the real vitreous cavity shape in studying uid motion induced by eye rotations. Modelling the vitreous cavity as a deformed sphere, showed that the flow field displays very complex three- dimensional characteristics to which effective fluid mixing is likely to be associated. The purpose of the thesis is to model numerically the motion of the liqueed vitreous within the vitreous cavity induced by different eye movements. Create the model in the Comsol interface, compare the results with theoretical, experimental measurements and do some ow visualizations. Finally show the dependence of the streaming intensity from the amplitude of rotations and the Womersley number .

The vitreous cavity, the largest chamber of the eye, is delimited anteriorly by the lens and posteriorly by the retina and is filled by the vitreous humour. Under normal conditions the vitreous humour has the consistency of a gel, however, typically, with advancing age a disintegration of the gel structure occurs, leading to a vitreous liquefaction. Moreover, after a surgical procedure called vitrectomy the vitreous body may be completely removed and replaced by tamponade fluids. Besides allowing the establishment of an unhindered path of light from the lens to the retina, the vitreous also has important mechanical functions. In particular, it has the role of supporting the retina in contact to the outer layers of the eye, and of acting as a diffusion barrier for molecule transport between the anterior and the posterior segments of the eye. Studying the dynamics of the vitreous induced by eye rotations (saccadic movements) is important in connection of both the above aspects. On the one hand indications exist that the shear stress exerted by the vitreous on the retina may be connected with the occurrence of retinal detachment. On the other hand, if the vitreous motion is intense enough (a situation occurring either when the vitreous is liqueed or when it has been replaced with a uid after vitrectomy), advective transport may be by far more important than diffusion and may have complex characteristics. Advection has indeed been shown to play an important role in the transport phenomena within the vitreous cavity, but, so far, only advection due to the slow overall fluid ux from the anterior to the posterior segments of the eye has been accounted for, while fluid motion due to eye rotations, even if it is generally believed to play an important role, has been invariably disregarded. Some recent contributions have pointed out the importance of accounting for the real vitreous cavity shape in studying uid motion induced by eye rotations. Modelling the vitreous cavity as a deformed sphere, showed that the flow field displays very complex three- dimensional characteristics to which effective fluid mixing is likely to be associated. The purpose of the thesis is to model numerically the motion of the liqueed vitreous within the vitreous cavity induced by different eye movements. Create the model in the Comsol interface, compare the results with theoretical, experimental measurements and do some ow visualizations. Finally show the dependence of the streaming intensity from the amplitude of rotations and the Womersley number .
Numerical study of the fluid motion and mixing processes in the vitreous cavity
Keywords: Comsol; fluid motion; vitreous cavity; saccadic movements; retinal detachment.; Comsol; fluid motion; vitreous cavity; saccadic movements; retinal detachment.